The whole truth about botulinum toxin – a review - Witmanowski, Henryk; Błochowiak, Katarzyna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2020)
Treatment with botulinum toxin is widely viewed as safe, effective and largely devoid of serious side effects. There are two classes of Botox-related adverse events – transient and benign events, and potentially serious events. The aim of this study was to provide an overview of Botox-related side effects and advise potential management and preventive strategies. Benign side effects are well-localized, reversible and self-limited complications which develop within a few days of the injection, and they usually disappear without any treatment. The aesthetic and functional adverse effects are associated with different muscle responses to botulinum toxin or with misplacement of botulinum toxin. The serious events are sequelae due to the systemic spread of toxin leading to botulism.